InnoCORE_Mapping of existing facilities V1 WP4 - Cerezo; Gırard; Schkade; Şahın; Pıngue; Raso; Negru; Lengyel; Cıofını (Zenodo, 2023)
The first aim of WP4 is to promote a fluid use and access of the existing research facilities for the EELISA community. To this end, the first task is focused on the identification and listing of the existing resources within EELISA. The facilities we will target are not only those already part of international network, but also technological platforms or resources developed by
EELISA partners willing to open them either in a collaborative or partnership fashion. This mapping will also allow to identify a network of facilities available for teaching purposes (ex.allowing the setup of teaching modules across the different platforms of the partners) both for a researcher and student public.
This work will provide a mapping (D4.1) that will be shared on the EELISA website and will contribute to the attractiveness of the Alliance. Increasing the visibility of the infrastructures will help in connecting researchers and in spreading the use of the specific procedures and methods developed by the EELISA partners, thus significantly contributing in enhancing their visibility. Furthermore, this network will allow the creation of a unique environment for teaching allowing students to access not only well-established instrumental setups but also state of the art research infrastructures and techniques in a large variety of fields.
To collect information needed for the mapping, a common survey was designed and distributed by the each EELISA partner among its academic staff and platform/technical managers to gather the information. To further motivate the feeding of the survey, it was presented in dissemination activities organized within EELISA. Finally, the group checked the quality of the data and suggested further actions to improve the catalogue and its usability for researchers.
The actual document of mapping is currently under revision and will be realised on the EELISA website in a few weeks following the publication of the present document.

DRAFT NOT YET APPROVED BY EUROPEAN COMMISSION
Keywords: Research facilities; Toolkit; EELISA InnoCORE; Open science; Guide